Análisis de amenazas y vulnerabilidades dentro del sistema de gestión del voluntariado en la Cruz Roja ubicada en la ciudad de Babahoyo - Cuesta Morante, Romina Isabel (2019)
The purpose of this case study is to analyze the web system "Red Cross Volunteer Management System" with the determination of finding possible threats and vulnerabilities that may jeopardize the organization's data or technological infrastructure. The methodology used for the development of this case study is the MAGERIT methodology, to discover the risks of the system, tools will be used for the analysis and to find possible system failures, the recommended tool for this type of analysis is Nessus, the quality provides an easy and simple interpretation of the results obtained. At the end of this document the policies and suggestions to improve the functionality of the organization as well as the conclusions and recommendations obtained in the investigation